Downstairs - Muhammad Helmi Ali. (2009)
A colloquial and affectionate term used by many when referring to the areas below their public housing blocks, “downstairs” is also the apt title for this Singaporean documentary. Unfolding over a 24-hour period, “downstairs” marries meaningful and colorful visuals with an audio collage to tell the personal stories of its users. With random and diverse profiles as supporting cast to the protagonist – “downstairs”, this high-definition short documentary shares anecdotes of community, love, dreams and memories. Moving from the rustic charms of the old neighborhoods to the swanky sophistication of the newer estates, it also documents change, in the form of transient meanings that exists between man and space. “downstairs” features heartwarming and candid displays of human interaction, sometimes tinged with innocent humor, showing how a space is not just a space but something that is full of life. With 81% of the Singaporean population living in public housing flats, “downstairs” is a peek into the nation’s culture and identity.